Emotion regulation of fear and disgust: differential effects of reappraisal and suppression. Issue 2 (17th February 2017) - Olatunji, Bunmi O.; Berg, Hannah E.; Zhao, Zidong
ABSTRACT: Although excessive fear has been central to traditional conceptualisations of the anxiety disorders, recent research suggests that disgust may also play a role in the development of some anxiety disorders. While dysregulation of emotion may confer risk for the development of anxiety disorders, it remains unclear if there are differences in the extent to which fear and disgust can be effectively regulated. To fill this important gap in the literature, unselected participants ( N  = 95) experienced fear or disgust via video exposure, and they were instructed to employ either reappraisal or suppression to regulate their emotional experience while viewing the videos. For those exposed to fear-relevant content, change in emotional distress did not significantly differ between those that suppressed and those that reappraised. However, significantly less emotional distress was observed for those that reappraised compared to those that suppressed when exposed to disgust-relevant content. Although physiological arousal varied over time as a function of the emotional content of the videos, it did not vary as a function of emotion regulation strategy employed. These findings suggest that reappraisal may be especially effective in regulating verbal distress when exposed to disgusting cues in the environment. The implications of these findings for the treatment of anxiety disorders that are characterised by excessive disgust reactions will be discussed.